Determination of diffusion coefficient in high temperature molten salt using cyclic voltammetry on microwire electrode: Its validity and limitation - Kim, Chan Mi; Yoon, Sung Pil; Cho, Sung Ki (ELSEVIER SCIENCE SA, 2021)
In this study, we developed a method for the determination of the diffusion coefficient (D) of electroactive species in high temperature molten salt without the knowledge of its concentration, via cyclic voltammetry at a simple unshielded microwire electrode. This method is based on the assessment of the ratio of the peak current (ip) of the cyclic voltammogram for its electrochemically reversible reaction at the microwire electrode, with ip at the macrowire electrode. The scan rate (nu)-dependent contribution of radial diffusion to ip at the microwire electrode provides a linear relationship between the ip ratio and nu-0.425, where its slope includes information on D. The theoretical evaluation with numerical simulation on this method revealed that possible underestimation in D determination could occur because of the minor contribution of radial diffusion at the macrowire electrode used in this study. D determination in the molten salt was experimentally verified with Eu3+ in 450 degrees C LiCl-KCl and O22- in 580 degrees C Li2CO3-Na2CO3. For both cases, the determined D values were similar to the reported values, and they were further cross-validated by calculating their concentrations from the D values. However, the accurate determination is limited for electrochemically reversible reaction as D is overestimated for quasi-reversible and totally irreversible reactions.
Keywords: OXYGEN REDUCTION; GLASSY-CARBON; VOLTAMMOGRAMS; TRANSIENT